Representasi Kelas Sosial: Studi Kasus dalam Film “Ranah 3 Warna” Karya Ahmad Fuadi: (Studi Analisis Semiotika Karl Max Mengenai Kelas Sosial) - Dita Nur Wulandari; Ilma Salsabilah Nafta (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
The film "Ranah 3 Warna" (Ranah 3 Warna) is adapted from the novel "Ranah 3 Warna" by Ahmad Fuadi. "Ranah 3 Warna" explores various aspects of human life. It depicts how differences in social class can lead to conflict. The researcher aimed to determine how social class is portrayed in the film. The purpose of this study was to determine how the film "Ranah 3 Warna" represents, displays, and conveys messages about social class. Based on this, the researcher chose this film for research and analysis using Karl Marx's class theory. This research method employed a qualitative research design with a descriptive study approach. Data collection in this study utilized library research. The approach used in this study was content analysis, with the researcher employing purposive sampling to obtain more in-depth data. The results of this analysis show scenes in the film that present social conflict through scenes and conflicts, particularly those involving the main characters. The Randai family represents the upper class and the Alif family represents the lower class, leading to several social inequalities.